Creative Work Beyond the Creative Industries: Innovation, Employment and Education - Rodgers, Jess; Hearn, Greg; Goldsmith, Ben; Bridgstock, Ruth (Edward Elgar, 2014)
'Hearn and his colleagues have amassed an impressive array of empirical evidence, theoretical insights and policy prescriptions for understanding how creative workers are contributing to a variety of industries outside the purely cultural or creative industry sectors. The scope of their investigations includes healthcare, banking, manufacturing, digital technology, creative services, journalism, media and communication, and higher education. This book significantly advances our understanding of how creative workers are utilizing their capabilities to contribute broadly to the economy.